Exchange Bias in Chemically Reduced FeCo Alloy Nanostructures. Issue 18 (17th July 2019) - Rajesh, Ponraj; Greneche, Jean-Marc; Jacob, G. Antilen; Arun, Thirumurugan; Joseyphus, R. Justin
Abstract : The equiatomic FeCo alloy with average particle sizes of 140 and 30 nm is obtained using an instant chemical reduction process. The mean hyperfine field of 36.0(5) T estimated from 300 K 57 Fe Mössbauer spectra is consistent with a disordered FeCo phase with a relative fraction of 90(2)% for both the samples, along with γ‐Fe2 O3 . A CoO shell with an average thickness of 2.7 nm is inferred from transmission electron microscopy in the size‐reduced FeCo. The room temperature coercivity of the size‐reduced FeCo is higher than the expected theoretical values. An exchange bias field ( H E of 296 Oe), vertical remanence shift at 15 K, and an exchange bias blocking temperature of 150 K are exhibited by the 30 nm FeCo particles. The observed H E and its temperature dependence are fairly explained based on a random field model. Abstract : The equiatomic FeCo alloy nanoparticles are synthesized through an instant chemical reduction process with the average particle sizes of 140 and 30 nm. The particles exhibit exchange bias, and the factors that affect the exchange bias field are explained invoking the random field model.